Utility of M-mode for assessment of grade 3 dyspneic patient - Yerramsetty, Venu Sashank; Ravikanti, Karthik; Kumar, Ranjith; Haward, Raymond (Halo 194 Scientific Journal of Emergency Medicine, 2024)
Respiratory distress is one of the leading diseases, and it can occur in those who are critically ill or who have significant injuries. It is often fatal, and the risk increases with age and severity of illness. So, early diagnosis of the causes of respiratory distress is an important process. But, the accurate diagnosis is challenging in this domain. So, to clinically achieve higher accuracy, in this diagnosis, the proposed study uses the Motion-mode echo parameters. This is a retrospective observational study.. The Mitral annular plane systolic excursion (MAPSE), tricuspid annular plane systolic excursion (TAPSE), , and E-Point to Septal Separation (EPSS). parameters of those admitted patient measurements are obtained. For analysis, this study totally considered 75 patients, in that 75, 46 were male and 29 were female. For all patients, the mean values calculated for MAPSE, TAPSE, EPSS were 13.463mm, 15.132 mm, and 9.4685 mm. The M-Mode parameter along with emergency physician clinical gestalt(M-mode model) was compared with the final diagnosis at discharge or death of the patient. The sensitivity, specificity, accuracy of the M-mode model was analysed considering the final diagnosis as the control. Key words: M-mode echocardiography, Mitral annular plane systolic excursion (MAPSE), tricuspid annular plane systolic excursion (TAPSE),  E-Point to Septal Separation (EPSS).